"We can regulate ourselves": Exploring the artisans' trade associations' contributions to occupational safety and health problem prevention. (October 2022) - Juliana Afolabi, Funmilayo
Highlights: The artisanal trade associations are involved in OSH management. The associations' organizational structure enabled the executives to exercise control over the members. The associations use soft rules in OSH management. The artisans' past experiences negatively affect their desire for monitoring and regulation of OSH by external agencies. Abstract: Occupational safety and health (OSH) problem prevention is a major concern in developing countries, especially for informal workers. However, little is known about the contribution of artisanal trade associations to OSH management. This qualitative study explores the contribution of informal workers' trade associations to OSH problems prevention. Twenty two executive members of the informal automobile artisans' trade associations from Osun State, Nigeria, were purposively selected and interviewed. The trade associations contribute to OSH problems prevention and management through monitoring, setting rules, and regulations that are binding on members. The identified areas of support from external bodies include the provision of modern equipment, mechanic village, prayers, and financial support. However, they are not willing to accept help for monitoring and regulations. The study concluded that in developing countries where there is an OSH management challenge for the informal workers, the trade associations could be used as intermediaries for regulating and disseminating OSH information to members.